MOLECULAR AND SEROLOGICAL DETECTION OF BOVINE ADENOVIRUS TYPE-3 IN BASRA PROVINCE - Shant Sinbat; Adnan Al-Rodhan; Rasha Othman (Basrah Journal of Veterinary Research)
Investigation of bovine adenovirus type 3 in symptomatic and asymptomaticcattle were carried out in this study ofdetecting circulating specific bovine adenovirustype 3 antibodies by Indirect ELISA and standard PCR technique. The studyexhibited these virus have detected by ELISA more than PCR technique. The resultswere showed thatthe overall seropositivity ratio of bovine adenovirus antibodies inanimals of Basra was (61.9%) and bovine fecal samples will tested byPCRwereonly seven fecal positive sample (6.1%) was found.